Hohenbergia amargosensis (Bromeliaceae: Bromelioideae), a new ornamental species from Bahia, Brazil - Souza, Everton Hilo De; Silva, Tiago Abreu Da; Aona, Lidyanne Y. S.; Souza, Fernanda V. D.; Leme, Elton M. C. (Phytotaxa, 2022)
The authors describe Hohenbergia amargosensis, a new ornamental species of Bromeliaceae from the Atlantic Forest of the Amargosa city, in Bahia state, Brazil. This new species is morphologically related to H. reconcavensis, but can be distinguished from it by the larger plant size when in bloom, longer inflorescence with laxly arranged branches, and a broader diameter at the base, primary bracts equaling to exceeding the primary branches, primary branches with longer stipe, and lilac petals. Additionally, its conservation status and phenology are discussed, and the illustrations of this new species and its morphologically close relatives are compared.